Methods for removal of resin remaining after debonding of orthodontic brackets: a literature review - Tonetto, Mateus Rodrigues; Frizzera, Fausto [UNESP]; Porto, Thiago Soares [UNESP]; Jordão, Keren Cristina Fagundes [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Santos, Reidson Stanley Soares dos; Klug, Rufino Jose; Bandeca, Matheus Coelho (SAGE Publications, 2014)
The removal of resin debris and/or resin cement from the enamel surface without causing iatrogenic is the main objective when removing the orthodontic brackets. Some factors such as the time required for removal, damage to the tooth structure, are essential factors for the clinician at the time of removal. Various techniques are used for the removal of orthodontic brackets after the treatment; it is known that the use of clinical procedures such as the use of diamond burs and some pliers removers can damage the structure of the enamel, often depending on the bond strength that should be taken into consideration at the time of removal. This literature review aims to gather the most relevant studies that can clarify the clinical technique, which may be more suitable for removal of the brackets.
Keywords: Adhesion; Brackets; Orthodontic